2019
DOI: 10.1177/0264619619839737
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life and related factors among older adults with visual impairments

Abstract: Aim was to explore the health-related quality of life (HRQoL) and related factors among older adults with visual impairment (VI). A total of 39 independently living subjects aged ⩾65 years (83 ± 6.5), referred to the Low Vision Center of the Oulu University Hospital, Finland during one year participated in the study. The participants had low vision or blindness as defined by the World Health Organization (WHO). The 15D, a generic HRQoL instrument, was used to assess the HRQoL, and an ophthalmic examination was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…This might explain the respondents' demands for better visual identification apps. The results agree with the findings of previous studies both in terms of difficulties faced by people with VI when using mobile devices (Damaceno et al, 2018) and the tasks that people with VI need mobile devices and applications for (Bhowmick & Hazarika, 2016;Hakobyan et al, 2012;Mednick et al, 2017;Riddering, 2016;Rodriguez-Sanchez et al, 2014;Siira et al, 2019).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This might explain the respondents' demands for better visual identification apps. The results agree with the findings of previous studies both in terms of difficulties faced by people with VI when using mobile devices (Damaceno et al, 2018) and the tasks that people with VI need mobile devices and applications for (Bhowmick & Hazarika, 2016;Hakobyan et al, 2012;Mednick et al, 2017;Riddering, 2016;Rodriguez-Sanchez et al, 2014;Siira et al, 2019).…”
Section: Discussionsupporting
confidence: 91%
“…People with VI encounter numerous challenges in everyday life, e.g. independent orientation, reading, retrieval of information, running errands, and social interaction (Bhowmick & Hazarika, 2016;Hakobyan et al, 2012;Mednick, Jaidka, Nesdolc & Bona, 2017;Riddering, 2016;Rodriguez-Sanchez, Moreno-Alvarez, Borromeo & Hernandez-Tamames,2014;Siira et al 2019). Being affected by VI also increases a person's risk of experiencing emotional and/or psychological burden (Mednick et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Quite unexpected, our results show that vision impairment and physical impairment have positive relation with quality of life which could be explained with greater support this people acquire from their families. Other studies showed different findings pointing that visual and hearing impairment had negative influence on quality of life [24,25] . However, when unique impact of health status on quality of life is analyzed, when other variables are controlled, health status explains 21.6% of variance in addition to variance explained by physical accessibility, socio-economic status and social environment.…”
Section: Discussionmentioning
confidence: 94%
“…Lower health satisfaction may be expected in this population, all of whom had a VI. VI and other chronic physical health conditions have been associated with poor health-related well-being and quality of life in older adults with a VI (Chia et al, 2004; Langelaan et al, 2007; Siira et al, 2019). In addition, many participants had a comorbid physical or mental health condition.…”
Section: Discussionmentioning
confidence: 99%